Early Childhood and Development Work
XV, 227 p.
Keywords: This edited volume provides a critical account of the theories and policies that have informed work in the field of early childhood and explores how they have operated in practice. Underpinning the theoretical debates are the familiar tensions between global norms and local contexts; increasing inequality alongside economic progress, and the increasing prominence of business and the private sector in delivering aid programs. The authors offer a profound critique on an increasingly important topic and discuss alternative models of policy and practice.